Effects of Enflurane on Histology of Liver and Kidneys in Rats - Yilmaz, Fethi; Timurkaan, Necati; Erhan, Omer Lutfi (Medwell Online, 2009)
The aim of this study was to assess the probable hepatic and renal histopathological changes in rats following a 2 h of enflurane administration, which is still used for anesthesia. A total of 20 Wistar rats were used in the study. The rats were classified randomly into 2 groups as control group and experimental group. The rats in the experimental group were anesthetized with 2% inhalational enflurane for 2 h. Following the anesthesia, sacrificed rats were subjected to necropsy and liver and kidneys were examined histopathologically. Histopathological changes in the experimental group included degenerative and necrotic changes and inflammatory cell infiltration. The kidneys were more affected compared to liver. Consequently, it was assessed that enflurane had significant effects on the histology of liver and kidneys. It was suggested that renal function should be taken into consideration while using this anesthetic agent.
Keywords: Enflurane; rat; kidney; liver; histopathology